The antiiflammatory effect of Ginkgo biloba in lipopolysaccharide-induced rat sepsis model - Ilhan, Nevin; Susam, Solmaz; Ak, Tuba Parlak; Baykalir, Burcu Gul (Walter de Gruyter Gmbh, 2018)
Background: Sepsis is characterized dysregulated inflammatory response and is the leading cause of organ failure or injury and death in critical care units. Ginkgo biloba extract 761 (EGb 761) is characterized by antioxidant activity. There is no clear data in the functional role of EGb 761 that inhibiting of proinflammatory cytokines exist in sepsis. The purpose of this study was to investigate the antiinflammatory effect of EGb 761 on the levels of vascular endothelial growth factor (VEGF), matrix metalloproteinase-9 (MMP-9) and inducible nitric oxide synthase (iNOS) in lipopolysaccharide (LPS) induced rat sepsis model. Methods: The animals were randomly divided into the following six groups: the control, LPS, flunixin meglumine (FM), EGb 761, LPS + FM and LPS + EGb 761 groups. Enzyme-linked immunosorbent assay (ELISA) analysis was applied to measure serum levels of VEGF, MMP-9, and iNOS. Results: Serum iNOs (p < 0.05), VEGF (p < 0.01) and MMP-9 (p < 0.05) levels were significantly higher in the sepsis group. Treatment with EGb 761 decreased serum iNOs levels (p < 0.01), VEGF and MMP-9 levels decreased significantly (p < 0.05). Also, treatment with FM decreased iNOs (p < 0.01), VEGF and MMP-9 levels significantly (p < 0.05). Conclusions: It is suggested that sepsis may lead to increase serum iNOs, MMP-9, and VEGF levels and treatment of EGb 761 may have a potential antiinflammatory effect against LPS-induced sepsis.
Keywords: flunixin; Ginkgo biloba extract; lipopolysaccharide; rat; sepsis